Keadilan Bagi Anak Berhadapan dengan Hukum Menurut Undang-Undang Nomor 11 Tahun 2012 tentang Sistem Peradilan Pidana Anak - Insan Firdaus (Badan Strategi Kebijakan Hukum, 2015)
The enactment of Law Number 11 of 2012 on juvenile criminal justice system on July 30, 2014, became beginning of a paradigm change in procedure and law enforcement officers in the handling of Children in Conflict with the Law. These changes put forward the completion of criminal cases involving child offenders, victims, family perpetrator / victim, and others to work together to find a fair settlement with emphasis on restoring victims and not merely retaliation. This study uses normative juridical approach by analyzing library materials that are used as the main ingredient, which include the primary legal materials, secondary, and tertiary associated with the process of dealing with juvenile justice law. Based on that through this paper the authors wanted to know how the position of juvenile criminal justice system in Indonesia and how the forms of justice for children in conflict with the law under the laws of the juvenile criminal justice system, and the role of law enforcement agencies in implementing the law. It can be concluded that the juvenile criminal justice system is part of the general judicial system that guide the implementation of the mechanism of justice for Children in Conflict with the Law. Justice for Children in Conflict with the Law Statutory juvenile criminal justice system not only not solely intended for the offender, but also to the victim with regard to the interests of the child. Therefore, the role of law enforcement officers directed the completion of criminal cases focus on supporting children through diversion to achieve restorative justice.